Use-Values for Inclusion: Mobilizing Resources in Popular Education for Newly Arrived Refugees in Sweden - Mešić, Nedžad (2019)
In times of market reforms and international migration, the Swedish welfare model has been seriously challenged. In the context of the arrival of refugees in 2015–2017, the state turned to civil society in facing up to the challenges. In this article, we direct our attention to the Workers’ Educational Association’s (ABF) state-funded work with refugees, with a specific focus on the activities conducted, the resources making them possible and the use-value of the resources mobilised. The article is based on observations and interviews with study circle leaders, managers and asylum seekers. The analysis illustrates that ABF, in line with its historical legacy, the broader workers’ movement, the strong notion of popular education as ‘free and voluntary’, has, with its well-established connections throughout the country, not solely taken on the task defined by the state. In solidarity, ABF has also responded to the needs of the refugees. As highlighted in the analysis, ABF has mobilized a wide range of resources, not least providing refugees with social networks and help in contacting the authorities. With such mobilization, opportunities were provided for the inclusion of refugees in Sweden.